Effect of Edaphic Factors on Mononchids in the Rhizophere of Polyhouse Grown Flower Crops (Indian Journal of Nematology, 2024)
Edaphic factors viz; soil pH, soil moisture, soil temperature and soil organic carbon, in relation to mononchid populations, revealed positive correlation between the two. Acidic soils in the pH range of 3.69-5.73 were found free from the mononchid populations, while a proportionate increase in their population was observed within a pH range of 5.78-6.58. However, after a pH above 7.0 there was recorded gradual decline in the population. Soil temperature between 20.6-23.0 0C supported higher populations of the predatory nematodes, while at low soil temperature (14.4-20.0 0C), the nematodes were absent/ low in the rhizosphere. Low soil moisture content (12.80-14.16%) did not support mononchid populations, while the nematodes were found prevalent at higher moisture levels (17.71-24.53%). Higher organic carbon contents (3.06-4.28%) supported higher mononchid population around the plant roots and vice versa.